FAM48A mediates compensatory autophagy induced by proteasome impairment. (3rd July 2019) - Arata, Yoshiyuki; Watanabe, Ayaka; Motosugi, Ryo; Iemura, Shun‐ichiro; Natsume, Tohru; Mukai, Kojiro; Taguchi, Tomohiko; Hirayama, Shoshiro; Hamazaki, Jun; Murata, Shigeo
Abstract: Maintaining protein homeostasis is central to cell survival. The ubiquitin–proteasome system and autophagy play pivotal roles in protein quality control through protein degradation. Activities of these degradative pathways are carefully orchestrated, and autophagy is up‐regulated during proteasome dysfunction for cellular homeostasis. However, the mechanism by which proteasome impairment induces compensatory autophagy has remained largely elusive. Here, we show that FAM48A mediates autophagy induction during proteasome inhibition. FAM48A is degraded by the proteasome and accumulates in cells by proteasome inhibition. Knockdown of FAM48A led to defective induction of autophagy during proteasome inhibition and accompanied by defective localization of Atg9 on recycling endosomes. Our results indicate that FAM48A is a kind of sensor that is required for compensatory autophagy induction upon proteasome impairment. Abstract : FAM48A mediates autophagy induction during proteasome inhibition. FAM48A is degraded by the proteasome and accumulates in cells by proteasome inhibition. Knockdown of FAM48A led to defective induction of autophagy during proteasome inhibition and accompanied by defective localization of Atg9 on recycling endosomes.